Challenges and Outcomes of Parallel Care for Patients with Co-Occurring Psychiatric Disorder in Methadone Maintenance Treatment - King, Van L. (2014)
OBJECTIVE: Most opioid users seeking treatment in community-based substance abuse treatment programs have at least one co-occurring psychiatric disorder, and the presence of psychiatric comorbidity in this population is associated with increased psychological distress, poorer quality of life, and reduced response to substance abuse treatment. This observational study describes clinical outcomes of referring patients receiving methadone maintenance and diagnosed with at least one co-occurring psychiatric disorder to a community psychiatry program located on the same hospital campus. METHODS: Participants (n=156) were offered priority referrals to a community psychiatry program that included regularly scheduled psychiatrist appointments, individual and group therapy, and enhanced access to psychiatric medications for one-year. Psychiatric distress was measured with the Symptom Checklist (SCL-90-R), which participants completed monthly. RESULTS: While about 80% of the sample (n=124) initiated psychiatric care, the average length of treatment was only 128.2 days (SD = 122.8), participants attended only 33% of all scheduled appointments (M = 14.9 sessions, SD = 14.1), and 84% (n = 104) did not complete a full year of care. Of those who did not complete a full year, almost two-thirds (65%, n = 68) left psychiatric care while still receiving substance abuse treatment. Exploratory negative binomial regression showed that baseline cocaine and alcohol use disorder (p = .002 and .022, respectively), and current employment (p = .034), were associated with worse psychiatric treatment retention. Modest reductions in psychiatric distress over time were observed (SCL-90-R Global Severity Index change score = 2.5; paired t = 3.54, df = 121, p = .001). CONCLUSIONS: Referral of patients with co-occurring psychiatric disorders receiving methadone maintenance to a community psychiatry program is often ineffective, even after reducing common barriers to care. Service delivery models designed to improve attendance and retention, such as integrated care models, should be evaluated. This study is part of a larger clinical trial, registered at www.clinicaltrials.gov under #NCT00787735.